Physicochemical and antioxidant properties of pectin from Actinidia arguta Sieb.et Zucc (A. arguta) extracted by ultrasonic - Liu, Liqi; Sui, Yuhan; Wang, Tienan; Li, Xiang; Chen, Lina; Shi, Mao (Frontiers in Nutrition, 2024)
Pectin was extracted from Actinidia arguta Sieb.et Zucc(A.Arguta) using ultrasound-assisted acid method and single acid method. The physicochemical properties, structure and antioxidant properties of two different pectins were investigated. The results showed that the extraction yield of the ultrasound-assisted acid method is higher than the single acid method. The molecular structure of A.Arguta pectin extracted by the ultrasound-assisted acid method belongs to a mixed structure of RG-I and HG type domain. Through structural feature analysis, the ultrasound assisted-extracted pectin(UAP) have more branched structure than the single acid-extracted pectin(SAP). The SAP has a higher degree of esterification than UAP. The physical property results show that the viscosity, solubility and water holding capacity of the UAP are better than the SAP. The antioxidant test resultsshow that the Hydroxyl radical scavenging and reducing power of the UAP are superior to the SAP.This study shows the composition, physicochemical properties and antioxidant activity of A.Arguta pectin extracted by ultrasonic-assisted extraction method in order to provide theoretical basis for its application as an antioxidant and other food additives in food industry.